Comparison of Z. N. staining & fluorescent microscopy in detection of M. Tuberculosis bacilli in Fine needle aspiration smears - Dr. Alpesh M. Maru; Dr. Dharmishtha N Kapadiy; Dr. Hardik Makavana; Dr. Nayna R. Lakum (Tropical Journal of Pathology and Microbiology, 2018)
Aims: To compare ZN stain method with Fluorescent method for detection of tuberculous bacilli in FNA smears in terms of sensitivity & feasibility. Settings and Design: A Prospective study was conducted in the department of Pathology at tertiary care center. FNAC done from lymph node lesion in clinically suspected cases of tuberculosis attending the Department of Medicine, Surgery, ENT, TB and Chest. Methods and Material: Fine-needle aspiration was performed in the Department of Pathology from January 2016 to February 2017. Out of 409 overall FNAC samples, there are 193 FNAC Lymph nodelesions, out of them 65 clinically suspected cases were processed for direct microscopy using conventional ZN staining and routine cytology and compared with the findings of the modified fluorescent method. Statistical analysis used: Simple statistical analysis done by using χ2 test. Results: Out of the 65 Tuberculous positive aspirates, the smear positivity for AFB on the ZN method was 43.07% (28/65) while the positivity increased to 87.69% (57/65) on the Auramine-Rhodamine fluorescent method. Conclusions: Fluorescent microscopy is rapid, simple, easy method with high detection rate for AFB as compared to ZN method.